Ecoliteracy Awareness of Elementary School Students in Waste Management - Karlina, Wili; Hartati, Tatat; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Waste management can be completed if humans have a sense of responsibility for the environment, an understanding of environmental conservation is called ecological intelligence (Ecoliteracy). The purpose of this study was to describe the ecoliteracy awareness of elementary school students in waste management. This study used the descriptive qualitative method. This study uses several data collection techniques including, questionnaires (questionnaires), interviews (interviews), and documentation. The participants in this study were five 3rd grade teachers and 26 3rd grade elementary school students. Documentation was conducted by analyzing two books concerning waste management. Data processing is done by analyzing the results of data collection and then describing to get a picture of the awareness of elementary school students in waste management. The results of the study show that: 1) from the interviews, it is known that the teacher has instilled an awareness of ecoliteracy in learning or outside of learning, but has never practiced recycling; 2) the results of the questionnaire show that students already have good knowledge of waste management, but their application is still lacking, and 3) the results of the documentation show that in the 3rd-grade books there are already quite complete waste management materials, but there are no student worksheets for making recycling projects. Ecolitercy awareness of elementary school students in waste management needs to be continuously instilled to form a generation that has environmental intelligence.